Quantifying the effects of far-red light on lettuce photosynthesis and growth using a 3D modelling approach - Li, Jiawei; Li, Yuanyuan; Chen, Yunke; Xu, Shipu; Wu, Xue; Wu, Cuinan; Zhang, Ningyi; Cao, Kai (Frontiers in Plant Science, 2024)
Supplemental far-red light has been extensively used for regulating plant growth in modern indoor plant production systems such as vertical farms. Despite an overall beneficial impact of far-red light on plant development and productivity, many studies demonstrated reductions of photosynthesis by far-red.Currently, the relative contribution of far-red to photosynthesis and plant growth in indoor production systems is not sufficiently quantified. This study aimed to quantify the photosynthesis and growth responses under different levels of supplemental far-red in lettuce, which is a common crop for indoor plant production. Lettuce were cultivated under a photoperiod of 16 hours with a photosynthetic photon flux density of 250 μmol m -2 s -1 of either white light or red to far-red (R:FR) ratio of 1.6 or 0.8.Measurements of plant morphological traits, leaf photosynthesis, and organ fresh and dry mass were taken at 7, 14, and 21 days after treatment. 3D representations of the lettuce plants were recreated based on 3D scanning technology, and the 3D modeling approach was used to simulate plant photosynthesis and biomass accumulation. Results showed that leaf elevation angle, leaf expansion rate, and lettuce fresh weight significantly increased at each growth stage as the R:FR ratio decreased. However, plants cultivated at low R:FR showed reduced leaf photosynthesis. Nevertheless, 3D model simulations demonstrated that plants exposed to enhanced far-red light exhibited increased light interception and whole-plant photosynthesis. In summary, far-red light-induced morphological changes enhanced light interception and whole-plant photosynthesis, thereby increased lettuce yield.